Empowering Sunten Jaya Village through interdisciplinary student synergy in community service - Indra Permana; Vivi Yantri; Isyfi Hadaina Yutikasari; Juni Ardiansyah; Ahmad Yoga Pratama; Annisa Firdaus; Asep Kusnadi (Universitas Pendidikan Indonesia, 2025)
Kuliah Kerja Nyata (KKN) is a program that is an integral part of the Tri Dharma Perguruan Tinggi, aimed at fostering social awareness and student responsibility toward community issues. This study examines the effectiveness of an interdisciplinary collaborative approach by Al Ghifari University’s KKN students in empowering the community of Kampung Patrol, Sunten Jaya Village, Lembang, West Bandung. Guided by the philosophy